2023
DOI: 10.1108/ijchm-10-2022-1319
|View full text |Cite
|
Sign up to set email alerts
|

Knowing how satisfied/dissatisfied is far from enough: a comprehensive customer satisfaction analysis framework based on hybrid text mining techniques

Abstract: Purpose This study aims to establish a comprehensive satisfaction analysis framework by mining online restaurant reviews, which can not only accurately reveal consumer satisfaction but also identify factors leading to dissatisfaction and further quantify improvement opportunity levels. Design/methodology/approach Adopting deep learning, Cross-Bidirectional Encoder Representations Transformers (BERT) model is developed to measure customer satisfaction. Furthermore, opinion mining technique is used to extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…However, research has shown that organization can attain their effectiveness through effective service delivery, and customer satisfaction (Yang et al,2024;Ayinaddis et al, 2023;Musa, 2023;Edeh et al, 2021a). It was this affirmation that service delivery and customer satisfaction were adapted as the indicators of organizational effectiveness in the hospitality industry.…”
Section: Organizational Effectivenessmentioning
confidence: 99%
See 3 more Smart Citations
“…However, research has shown that organization can attain their effectiveness through effective service delivery, and customer satisfaction (Yang et al,2024;Ayinaddis et al, 2023;Musa, 2023;Edeh et al, 2021a). It was this affirmation that service delivery and customer satisfaction were adapted as the indicators of organizational effectiveness in the hospitality industry.…”
Section: Organizational Effectivenessmentioning
confidence: 99%
“…Thus, for the hospitality industry to be effective, service delivery to customers must be prompt and tangible. Service delivery is an indicator of organizational effectiveness and performance (Yang et al,2024). When customers demand services in the hospitality industry, it is the responsibility of the service providers to make their requests promptly if not they will not be satisfied, and this will affect the profits of the organization (Edeh et al, 2021b).…”
Section: Organizational Effectivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al (2015) later solidified that positive and negative emotions are indeed distinct variables that coexist in restaurant settings. In addition, recent big data studies in a restaurant context (Liu et al , 2022; Mehraliyev et al , 2020; Yang et al , 2023) have also confirmed that positive and negative emotions have distinct roles, and further studies on what constitutes specific emotions and how they affect satisfaction and behavior are necessary.…”
Section: Introductionmentioning
confidence: 97%